Some remarks on generalized sequence space of bounded variation of sequences of fuzzy numbers - Altinok, H.; Et, M.; Colak, R. (University of Sistan and Baluchestan, 2014)
The idea of difference sequences of real (or complex) numbers was introduced by Kizmaz [8]. In this paper, using the difference operator and a lacunary sequence, we introduce and examine the class of sequence bv? (?, F). We study some of its properties like solidity, symmetricity, etc. © Iranian Journal of Fuzzy Systems
Keywords: Difference operator; Fuzzy number; Lacunary sequence